2022
DOI: 10.1002/mp.15847
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric multiphase ventilation imaging based on four‐dimensional computed tomography for functional lung avoidance radiotherapy

Abstract: Purpose Current computed tomography (CT)‐based lung ventilation imaging (CTVI) techniques derive a static ventilation image without temporal information. This research aims to develop a four‐dimensional CT (4DCT)‐based multiphase dynamic ventilation imaging framework capable of recovering the entire ventilation process throughout the breathing cycle for functional lung avoidance radiotherapy (FLART). Methods A total of 15 free‐breathing thoracic 4DCT scans of lung or esophageal cancer patients were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…At present, many examinations can provide detailed distribution information of lung function, including proton lung MRI 9 , phase-cycled balanced SSFP (bSSFP) acquisition MRI 10 12 , hyperpolarized gas (HPG) MRI 13 , Electrical impedance tomography (EIT) 14 , 15 . Fourier decomposition magnetic resonance imaging (FD-MRI) 16 18 , SPECT/CT 2 , 18 21 , 4D-CT 22 27 , multimodal imaging 28 , and it is applied in radiotherapy planning to avoid higher damage to high-function organs 29 32 . Among these examinations, 4D-CT is the most popular 33 , 34 , the operation is the simplest, and the radiation needed to be received is low.…”
Section: Discussionmentioning
confidence: 99%
“…At present, many examinations can provide detailed distribution information of lung function, including proton lung MRI 9 , phase-cycled balanced SSFP (bSSFP) acquisition MRI 10 12 , hyperpolarized gas (HPG) MRI 13 , Electrical impedance tomography (EIT) 14 , 15 . Fourier decomposition magnetic resonance imaging (FD-MRI) 16 18 , SPECT/CT 2 , 18 21 , 4D-CT 22 27 , multimodal imaging 28 , and it is applied in radiotherapy planning to avoid higher damage to high-function organs 29 32 . Among these examinations, 4D-CT is the most popular 33 , 34 , the operation is the simplest, and the radiation needed to be received is low.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies revealed that temporary lung function defects exist and their function may recover after or during treatment (Yuan et al 2012), necessitating future investigations to identify such temporary defects pretreatment and protect them when making treatment plans. Additionally, the use of free-breathing images fails to fully capture the influence of respiratory motion on the derived lung function maps (Huang et al 2022b), and the imperfect registration between SPECT and planning CT images may result in inconsistencies between the generated and actual lung function maps (Yin et al 2010). However, the proposed AP-FLART is also applicable to other lung function mapping techniques that may mitigate these challenges.…”
Section: Discussionmentioning
confidence: 99%
“…One ongoing phase 2 trial demonstrates 4D CT-guided ventilation as a useful clinical application in functional avoidance in patients with at least grade 2 radiation pneumonitis ( 59 ). Similar clinical trials are being conducted globally to optimize radiation therapy in lung cancer patients, like understanding lung ventilation physiology in chest radiation treatment, while still decreasing radiation dose administration, reducing tumor burden, and preserving ventilation ( 60 , 61 ).…”
Section: Applications Of Functional Lung Imagingmentioning
confidence: 99%